Absolving the American guilt: forgiveness and purification in Clint Eastwood’s cinema - Antonio Sánchez-Escalonilla (Church, Communication and Culture, 2021)
The guilt-ridden character archetype is a recurring premise in Clint Eastwood’s cinema, recognizable in the inner conflicts of the protagonists of iconic titles, such as Unforgiven (1992), Mystic River (2003), Million Dollar Baby (2004) and Gran Torino (2008). According to Scott, Unforgiven marks the beginning of the filmmaker's authorship stage, where scenarios of diverse genres, such as road movie, war cinema or gangster plots introduce protagonists who coincide in their need for purification. This paper aims to explore the construction of characters carried out in the four titles aforementioned, by means of a script analysis methodology based on the dynamics of conflicts and on the classic concepts of hybris, hamartia and catharsis. This analysis points to a double purpose. On the one hand, it highlights the purification sought by the protagonists of Clint Eastwood and its relationship with the Christian moral context in which the characters arise, as Roche & Hösle notice. On the other hand the analysis points out the social extension of the concept of catharsis addressed by the filmmaker, especially critical when exposing the fragility of the American Dream and its modern traumas.